2020
DOI: 10.1101/2020.11.17.20210211
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The impacts of COVID-19 mitigation on dengue virus transmission: a modelling study

Abstract: SummaryBackgroundThe COVID-19 pandemic has induced unprecedented reductions in human mobility and social contacts throughout the world. Because dengue virus (DENV) transmission is strongly driven by human mobility, behavioral changes associated with the pandemic have been hypothesized to impact dengue incidence. By discouraging human contact, COVID-19 control measures have also disrupted dengue vector control interventions, the most effective of which require entry into homes.MethodWe used an agent-based model… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
(64 reference statements)
1
0
0
Order By: Relevance
“…Nonetheless, the group-level shift towards peridomestic activities and increased tick exposure indicates either an increase in the overall tick population or increased exposure in those settings where participants are less inclined to use preventative measures against tick bites 30 . A similar pattern was observed for mosquito-borne disease in two studies on dengue infection: i) a simulation model found that COVID-19 stay-at-home measures (in which 70% of the population restricted their mobility to their house) led to an increase in overall infections and increased clustering of cases at the household level 42 ; and b) an empirical study using dengue case report data in Singapur found a 37.2% increase in the number of cases from expected baseline levels attributed to COVID-19 stay-at-home measures 43 .…”
Section: Discussionsupporting
confidence: 67%
“…Nonetheless, the group-level shift towards peridomestic activities and increased tick exposure indicates either an increase in the overall tick population or increased exposure in those settings where participants are less inclined to use preventative measures against tick bites 30 . A similar pattern was observed for mosquito-borne disease in two studies on dengue infection: i) a simulation model found that COVID-19 stay-at-home measures (in which 70% of the population restricted their mobility to their house) led to an increase in overall infections and increased clustering of cases at the household level 42 ; and b) an empirical study using dengue case report data in Singapur found a 37.2% increase in the number of cases from expected baseline levels attributed to COVID-19 stay-at-home measures 43 .…”
Section: Discussionsupporting
confidence: 67%